Non-structural Preparedness Analysis At RSUP Dr. Mohammad Hoesin In Disaster Based On The Hospital Safety Index - Yenni, Ririn Afrima; Novrikasari, N; Windusari, Yuanita (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2020)
Disasters are one of the most challenging cases for health institutions that can disrupt health services’ functioning. However, as essential and primary care providers in society, health institutions and especially hospitals must be prepared for disasters and emergencies. This study analyzes the hospital’s non-structural preparedness in facing disasters based on the Hospital Safety Index in RSUP (Central General Hospital) Dr. Mohammad Hoesin. This research is a mixed-methods study with a sequential explanatory design. The research subjects were four people. The key informants consisted of Occupational Health and Safety Staff and Non-Medical Facilities Maintenance Staff. The triangulation informant was the Occupational Safety and Health Committee. The non-structural preparedness of RSUP Dr. Mohammad Hoesin, based on the Hospital Safety Index is 0.84. The results of the in-depth interviews show that the obstacles for hospitals in implementing disaster preparedness are budgetary funds and the focus of the hospital in improving structural preparedness and health services. RSUP Dr. Mohammad Hoesin is at a high level of non-structural preparedness. Overall, the hospital can function in emergencies and disasters. However, it is recommended to continue with steps to improve crisis and disaster management's security and capacity.  Abstrak: Bencana adalah salah satu kasus paling sulit bagi institusi kesehatan yang dapat mengganggu fungsi layanan kesehatan. Namun, sebagai dasar dan penyedia perawatan primer dalam masyarakat, institusi kesehatan dan khususnya rumah sakit harus siap menghadapi bencana dan keadaan darurat. Penelitian ini bertujuan untuk menganalisis kesiapsiagaan nonstruktural rumah sakit dalam menghadapi bencana berdasarkan Hospital Safety Index di RSUP Dr. Mohammad Hoesin. Penelitian ini merupakan penelitian mix methods dengan jenis sequential explanatory design. Subjek penelitian berjumlah empat orang. Informan kunci terdiri dari Staf Keselamatan dan Kesehatan Kerja dan Staf Instalasi Pemeliharaan Sarana Non-Medik (IPSNM). Informan triangulasi yaitu Komite Keselamatan dan Kesehatan Kerja. Kesiapsiagaan nonstruktural RSUP Dr. Mohammad Hoesin berdasarkan Hospital Safety Index sebesar 0,84. Hasil wawancara mendalam menunjukkan bahwa kendala rumah sakit dalam menerapkan kesiapsiagaan bencana yaitu anggaran dana, serta fokus rumah sakit dalam tahap peningkatan kesiapsiagaan struktural dan pelayanan kesehatan. RSUP Dr. Mohammad Hoesin berada pada level kesiapsiagaan nonstruktural tinggi. Secara keseluruhan rumah sakit dapat berfungsi dalam keadaan darurat dan bencana. Namun, direkomendasikan untuk melanjutkan langkah-langkah dalam memperbaiki tingkat keamanan dan kapasitas penanganan darurat dan bencana.